Effect of film thickness on hysteresis of narrowband thermochromic liquid crystal - Mohd Zulkeple, Muhammad Fitri (2020)
Thermochromic liquid crystal (TLC) is a complex substance with a unique optical property as the function of temperature. However, due to the different TLC sample preparations, which may have a different composition and undefined proper thickness estimation method, the calibration of TLCs might be different, which can lead to the hysteresis. Therefore, research to investigate the effect of several approaches of factors on the calibration of narrowband TLC for thermography purpose was conducted. This will be helpful to the user who uses narrowband TLCs for thermography. The estimation of the TLC thickness was done based on the dry solid content method, where it involves several weighting step of wet and dry TLCs. This method was found to provide consistency with a relatively low percentage of 0.2 % to 4.0 % difference between the actual and the estimated one. However, it should be noted that this difference percentage was vary depending on the mixing type and the coating applying method. There were three samples with different compositions been used in the baseline test of the current study to find the best TLCs that can provide the best performance based on several criteria. The sample, which has a higher composition of TLC, was observed to produce brighter colour intensity. In contrast, the binder which was added to the sample provides extra protection to the TLCs from the heat stress by the repeated heating and cooling cycles, also the aging effect. As the best performance the TLC sample has been chosen, that particular TLC sample will be further tested in terms of the occurrence of hysteresis. For the peak temperature, the hysteresis level becomes higher as the peak temperature increased. This is because, beyond the clearance point, the TLCs were in the isotropic states where the focal conic texture, which was not optically activated, tends to form. As for the bandwidth, broader bandwidth has a lower hysteresis compared to the narrower bandwidth. For TLC with the bandwidth of 1 ℃, when been cooled from 52 ℃, the level of hysteresis was 59 %, which was larger compared to the TLCs with the bandwidth of 2 ℃ and 3 ℃ in which has 44 % and 23 % of of hysteresis level respectively. This shows that broader bandwidth TLCs have higher resistivity towards the hysteresis. This was because broader bandwidth can transmit more information, which means that the colour information during the colour play as the temperature increases most likely can be harvested. Finally, for the thickness approach, for the condition where the TLCs have been cooled from the clearance point (52 ℃), the decline pattern of the hysteresis can be seen clearly for thickness range of 10 μm to 90 μm. This shows that thicker coating has more resistance toward the hysteresis due to the anchoring force, which might help to retain the elastic forces of the helical stature as been stated and supported by many pieces of literature.